Perancangan Sistem Informasi E- Library Menggunakan UML model Berbasis Client Server - Basiroh; Widya Novita Al-Afifah Irwanto (Tekompedia : Jurnal Ilmiah Ilmu Komputer, 2025)
Various information systems are currently experiencing rapid development, one of which is desktop-based, this system is one of the things that will be adopted for library data management activities in schools. Currently, the library system at one of the State Junior High Schools in Prambanan still uses the method of writing guest books to manage library data. One thing that is still being done today is writing borrower data, book data, and visitor data. Library staff record data on students who borrow books, the possibility of the book being returned but not recorded, or returned damaged or lost. Designing a library system using UML is designed to meet system deficiencies. The results of the library information system are expected to make it easier for students to obtain the desired book information. Officers can search through the existing system in library management to borrow books in a relatively quick and structured manner. The book return process is well-systemized